2012
DOI: 10.1371/journal.pone.0036887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression among Outpatients with Type 2 Diabetes in the Mexican Population

Abstract: BackgroundDepression and anxiety are common in diabetic patients; however, in recent years the frequency of these symptoms has markedly increased worldwide. Therefore, it is necessary to establish the frequency and factors associated with depression and anxiety, since they can be responsible for premature morbidity, mortality, risk of developing comorbidities, complications, suffering of patients, as well as escalation of costs. We studied the frequency of depression and anxiety in Mexican outpatients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
77
5
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 30 publications
11
77
5
11
Order By: Relevance
“…The prevalence of anxiety in the current study was higher than other studies; for example, in a study conducted in Mexico, the prevalence of anxiety in diabetic patients was 52.9% (25). Regarding the difference in the prevalence of anxiety and depression, it can be stated that anxiety and depression have epidemic progress and this trend emerges in the shape of the society's mental characteristics (26).…”
Section: Discussioncontrasting
confidence: 69%
“…The prevalence of anxiety in the current study was higher than other studies; for example, in a study conducted in Mexico, the prevalence of anxiety in diabetic patients was 52.9% (25). Regarding the difference in the prevalence of anxiety and depression, it can be stated that anxiety and depression have epidemic progress and this trend emerges in the shape of the society's mental characteristics (26).…”
Section: Discussioncontrasting
confidence: 69%
“…Prevalence rates of clinically significant anxiety among individuals with diabetes range from 14% in a comprehensive review 6 to 55.10% in a Mexican population. 20 One study found that clinically significant anxiety was 20% higher among Americans with diabetes, compared to Americans without diabetes, after controlling for age, smoking, education, employment, physical activity, body mass index (BMI), and marital status. 21 Additionally, rates of GAD and phobias are considerably higher among diabetic populations when compared to community samples.…”
Section: Introduction Disparitiesmentioning
confidence: 99%
“…Recientes estudios muestran que en los pacientes con diabetes, el riesgo de sufrir algún tipo de malestar psicológico con síntomas de depresión y ansiedad es aproximadamente el doble que en la población normal (Buchberger et al, 2016;Tovilla-Zárate et al, 2012;Trento et al, 2012).…”
unclassified
“…Dichos síntomas parecen tener relación con otras condiciones y circunstancias de la diabetes; así, la ansiedad se asocia con dificultades en el autotratamiento de la enfermedad (Fisher et al, 2010) y la aparición de polineuropatía diabética periférica, los indicadores de severidad de la misma, los síntomas asociados y la repercusión de esta complicación en las actividades de la vida cotidiana ocasionan con el tiempo un incremento de los síntomas depresivos (Vileikyte et al, 2009). Además, las complicaciones de la diabetes, en general, se asocian tanto con síntomas de ansiedad como de depresión (Chien & Lin, 2016;Tovilla-Zárate et al, 2012). Por todo ello, parecen existir factores relacionados con la enfermedad y sus repercusiones funcionales que contribuyen al desarrollo de malestar psíquico; estos factores deben ser tenidos en cuenta a la hora de plantear intervenciones que mejoren dicho malestar en estas poblaciones (González et al, 2011;Usán, Salavera, Murillo, & Mejías, 2016;Vidal-Peracho et al, 2014).…”
unclassified